PHYSICAL EDUCATION AND THE NVIVO SOFTWARE IN QUALITATIVE RESEARCH: A BIBLIOMETRIC STUDY - Farias, Alison Nascimento [UNESP]; Pucinelli, Ricardo Henrique; Impolcetto, Fernanda Moreto [UNESP] (Ludomedia Unipessoal Lda, 2023)
In Physical Education, in recent years, there has been an increase in qualitative research, despite the greater prevalence of studies being quantitative. Linked to this expansion, the use of software to support qualitative data has emerged to assist researchers in systematizing and analyzing data. In this sense, this article aimed to highlight information about the scientific panorama of the NVivo software in Physical Education, bringing discussions, trends, and the realization of new research that may contribute to the advancement of the theme. The methodological approach was mixed (quantitative and qualitative) through VOSviewer bibliometrics and NVivo. The main results point to an increase in qualitative research in Physical Education using the NVivo software. However, the number of 60 registrations seemed below expectations. There is a prevalence of Spain, Brazil, and the USA in most of the production of knowledge in this area, with emphasis on three Brazilian researchers in collaboration networks with other authors in the subject in question. Furthermore, English was the language with the highest number of records in the articles found, followed by Spanish and Portuguese. It was found that Brazil is the second country that most publish on the subject analyzed. It was also possible to verify that three Brazilian universities are the ones that have produced the most: the State University of Santa Catarina; the State University of Western Paraná and the State University of Maringá. We emphasize that the use of NVivo is expanding, and that this software can be an excellent tool to assist researchers in their investigations, especially in the systematization and analysis of qualitative data.
EDUCAÇÃO FÍSICA E O SOFTWARE NVIVO EM PESQUISAS QUALITATIVAS: UM ESTUDO BIBLIOMÉTRICO
Keywords: Bibliometrics; Physical Education; Qualitative research; Quantitative Analysis